2013
DOI: 10.1371/journal.pone.0081679
|View full text |Cite
|
Sign up to set email alerts
|

Meta-Modeling of Methylprednisolone Effects on Glucose Regulation in Rats

Abstract: A retrospective meta-modeling analysis was performed to integrate previously reported data of glucocorticoid (GC) effects on glucose regulation following a single intramuscular dose (50 mg/kg), single intravenous doses (10, 50 mg/kg), and intravenous infusions (0.1, 0.2, 0.3 and 0.4 mg/kg/h) of methylprednisolone (MPL) in normal and adrenalectomized (ADX) male Wistar rats. A mechanistic pharmacodynamic (PD) model was developed based on the receptor/gene/protein-mediated GC effects on glucose regulation. Three … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 51 publications
0
7
0
Order By: Relevance
“…Blood glucose homeostasis is sustained mainly through the balance between hepatic glucose output (HGO) and glucose uptake primarily by brain, muscle and adipose tissue [67]. Liver is the major site for gluconeogenesis and also a primary metabolic target of CS.…”
Section: Pepck-insulin-glucose Dynamicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Blood glucose homeostasis is sustained mainly through the balance between hepatic glucose output (HGO) and glucose uptake primarily by brain, muscle and adipose tissue [67]. Liver is the major site for gluconeogenesis and also a primary metabolic target of CS.…”
Section: Pepck-insulin-glucose Dynamicsmentioning
confidence: 99%
“…The current model is limited in that the roles of skeletal muscle and adipose tissue in the development of insulin resistance, which also contribute to increases blood glucose were not accounted for. While a multi-organ model of glucose regulation by transcriptomic CS actions has been reported [67], our goal in this analysis was to link protein-level measures to PD outcomes. While the present model could adequately predict glucose and insulin dynamics from a different acute dosing study (Fig.…”
Section: Pepck-insulin-glucose Dynamicsmentioning
confidence: 99%
“…Routine treatment of MS relapse with methylprednisolone induces an unfavorable effect leading to the increase of leptin concentration. Experimental studies showed similar effects of methylprednisolone infusion on plasma leptin concentration [32] with subsequent metabolic effects in adipose tissue and skeletal muscles leading to limitation of insulin-mediated glucose utilization. In another experimental study, the peak plasma leptin concentration appeared 12 hours after methylprednisolone infusion [33].…”
Section: Discussionmentioning
confidence: 92%
“…As the complexity of a pharmacodynamic model increases and becomes mechanistically-based, many parallels can be drawn from the methodology and concepts associated with systems biology models (Danhof et al, 2008). In that context, the examples of indirect effect, transduction and transit models, tolerance models, and feedback mechanisms (Fang et al, 2013; Hazra et al, 2007; Jin et al, 2003; Jin & Jusko, 2009; Sukumaran et al, 2011) adapt basic elements of reaction kinetics towards revealing the exposure-response relationship of a drug.…”
Section: Pharmacodynamic Modelsmentioning
confidence: 99%